Sidney Mintz: Sweetness and Power - Lazar, Žolt K. (Sociološki pregled, 2019)
Sweetness and Power, the most famous study of American anthropologist Sidney Wilfred Mintz (1922-2015), is at the same time one of the most important historicalanthropological works of the second half of the 20th century.